Review of the British Thoracic Society Winter Meeting 2013, 4–6 December, London, UK. Issue 4 (8th March 2014) - Chalmers, James D; Greening, Neil J; José, Ricardo J; Janes, Samuel M; ,
Abstract : This article reviews the British Thoracic Society Winter Meeting 2013, the annual scientific meeting attended by over 2000 delegates and representing the depth and breadth of UK respiratory medicine. This year's meeting from 4 to 6 December in London featured cutting-edge research alongside keynote symposia from international experts in respiratory science, epidemiology and clinical trials. This article reviews the key symposia and selected abstract sessions from the 2013 meeting.